From video observation to in situ observation of teachers’ work in difficult situations: a study of effects on students teachers - Ria, Luc; Serres, Guillaume; Leblanc, Serge (Swiss Journal of Educational Research, 2010)
The article describes and analyzes the effects of the observation phase used during the training course run by a French secondary teacher’s education and training institute. This observation phase is aimed at helping students to prepare for their first teaching job.Students are successively confronted with difficult teaching situations first by watching them on video, them by observing them in situ. In order to foster their own learning process, students are then invited to describe their emotions, perceptions and reflections on the different observations made of their performances. Results show that there is potential for students to learn through this observation phase; but they also reveal the necessity of honing the students’ analytical skills in order for this phase to contribute significantly to their professional development.